Dermatological conditions in skin of colour. Issue 8 (August 2022) - Pathak, Anjali; Perry, Michael
The UK has rapidly diversifying demographics in common with most advanced, globalised economies. There is therefore an emerging, integral need for clinicians to recognise and manage skin and hair conditions across all ethnicities. When we discuss skin of colour, we refer to a spectrum of diverse geographic ancestral origins, including, but not limited to, those of Asian, African, Middle Eastern or Hispanic/Latino descent, as well as people of mixed heritage. Patients with darker skin phototypes (Fitzpatrick IV-VI) may experience additional complications and present differently to lighter skin counterparts. Knowledge of these nuances will undoubtably lead to better care and outcomes for patients. In this article, we explore skin and hair conditions that are common and important in patients with skin of colour.